2017
DOI: 10.1017/s1751731116001373
|View full text |Cite
|
Sign up to set email alerts
|

Beef palatability and its relationship with protein degradation and muscle fibre type profile in longissimus thoracis in Alentejana breed from divergent growth pathways

Abstract: The traditional beef production in the South of Portugal is based on a discontinuous growth (DG) system that requires lower external inputs and could enhance meat quality and financial returns to cattle producers. This system allows farmers to take advantage of the bull's compensatory growth when the pasture is abundant and finishes the cattle on concentrates for 2 to 3 months before slaughter. The fast gain rate before slaughter could be a valuable strategy to improve tenderness and to reduce its inconsistenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Their relative fiber type compositions can influence appearance quality traits (AQT, such as meat color, drip and purge loss, and amount of intramuscular fat) and eating quality traits (EQT, such as tenderness, flavor, juiciness, and palatability) ( Joo et al , 2013 ). Although many studies have reported fiber type compositions in various cattle breeds ( Calkins et al , 1981 ; Costa et al , 2017 ; Hwang et al , 2010 ; Ozawa et al , 2000 ; Totland et al , 1988 ), very few studies have investigated fiber type compositions in Hanwoo cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Their relative fiber type compositions can influence appearance quality traits (AQT, such as meat color, drip and purge loss, and amount of intramuscular fat) and eating quality traits (EQT, such as tenderness, flavor, juiciness, and palatability) ( Joo et al , 2013 ). Although many studies have reported fiber type compositions in various cattle breeds ( Calkins et al , 1981 ; Costa et al , 2017 ; Hwang et al , 2010 ; Ozawa et al , 2000 ; Totland et al , 1988 ), very few studies have investigated fiber type compositions in Hanwoo cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in live weight gain, feed intake, and animal performance are described in detail by Costa et al [ 13 , 22 ]. Briefly, the average daily gain (ADG) from 9 to 15 months of age was 1678 g/day and 99 g/day in CG and DG bulls, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sensory attribute, which is more correlated with the overall liking of steak, for US consumers, is the flavour liking (Hunt et al, 2014;Corbin et al, 2015), even before tenderness and juiciness (O'Quinn et al, 2012). Nevertheless, other studies verified that global acceptance has a higher correlation with tenderness and juiciness and a low correlation with flavour (Costa et al, 2016). These contradictory results found in the literature are comprehensible as both factors have such importance such as 'if the flavour is not acceptable, beef is rejected regardless of the other attributes', and the same happens to tenderness 'if tenderness is not acceptable, beef is rejected regardless the other attributes'.…”
Section: Flavourmentioning
confidence: 99%